Changing Scenario of Forests in Tripura - Ghosh, A. K. (Indian Forester, 1992)
Tripura, which attained statehood in 1972, is the second smallest State in India, with a geographical area of 10940 km2. (approx). The State is situated in the sub-tropical zone with rainfall distributed over six months a year and edapho-climatic conditions ideally suited for tropical forestry. It was a Hindu State 4 of great antiquity, dating back 1300 years, ruled by Tripuri Kings of single dynasty before its accession to the Indian Union in October, 1949. It was primarily a tribal majority State comprised of different ethnic tribal communities whose main source of livehood was from jhuming. During the past one hundred years, the population, mostly comprising of Bengali Hindu migrants, particularly after independence, has risen from 75000 to more than 2.70 million, which has resulted in the proportion of tribal population falling from 65 percent to a little over 28 per cent at present. Due to reduced forest area available to the tribal population, jhuming which most of them still practise, has become unproductive and uneconomic and is resulting in severe destruction of forests in the hills. The forests have also been subjected to extensive fellings due to increased requirement of timber and fuelwood for the large population. This has resulted in the retrogression of forest vegetation which was once a climatic climax of Tropical evergreen forests to the degraded fire climax that it is at present.